(untitled) (Journal of Pure & Applied Sciences, 2024)
In this study, two software MBAL - Petroleum Experts and Eclipse are used to do comprehensive reservoir study for LCSF plane of development, this study covered analyses and evaluation. Gas injection essentially increases the rate of oil field development and in many cases permits increased oil recovery. This paper demonstrates a successful simulation case study based on a field data of a project. The objective of this study is to improve recovery from Libyan Carbonate Sedimentary Field by three wells of gas injection. To do that, first, the simulation 3-D model was built by using advanced reservoir simulation software (Schlumberger Eclipse). Second, select the best zone for gas injection. Third, select the best location for injector well. Fourth, determine the injector well depth. The results of the paper can be seen to match the real data of the reservoir with the results of the program using a MBAL software. The simulator results show the reservoir pressure history curve is matching to the stimulation curve, this gives a good allusion of the input data that has been entered to the model. The driving mechanism of this reservoirs it comes from three natural forces, which are fluid expansion, PV compressibility, and water influx. Gas injection scenario has a good plateau bpd lasts approximately 3 years and after that started to decrease. The Cumulative oil production is 108442340 STB barrels of oil with the recovery factor approximately 0.52805 and final reservoir pressure is maintained 328.76 pisa